Faculty Development Program (FDP) Of Selected Private Colleges In General Santos City: Its Impact On Organizational Commitment And Adaptive Performance, Basis For Enhanced Retention Program (International Journal of Scientific Research and Management (IJSRM), 2024)
The purpose of this study was to determine How faculty Development Program affected the organizational commitment and adaptive performance of faculty members among selected private Higher Educational Institutions in General Santos City. The overarching objective of the program was to develop an intervention designed to yield an intervention program that will help increase if not sustain the above-variables of the study. The research utilized an adapted 4-part questionnaire to assess 104 faculty members, investigating the impact of Faculty Development Programs (FDP) on organizational commitment and adaptive performance. Employing a descriptive-correlational research design, the study employed the Input-Process-Output (IPO) paradigm to thoroughly analyze each variable, supported by a comprehensive review of related literature. Statistical analysis including frequency counts, percentages, mean, standard deviation, t-test, ANOVA, and Pearson r revealed that FDP positively influenced professional development, teaching skills, leadership, classroom management, knowledge and skills, and organizational participation. Respondents demonstrated moderate affective commitment, high continuance commitment, and moderate normative commitment, alongside adaptive behaviors in handling emergencies, managing work stress, problem-solving, and interpersonal, cultural, and physical adaptability. Based on these findings, a recommended intervention program in the form of a training workshop aims to further enhance faculty development.